Adolescent Psychology Psychoeducation for Children of Indonesian Migrant Families in Malaysia - Irianti Usman; Winy Nila Wisudawati; Wiwik Sulistyaningsih; Fransisda Tiodora Ferdiansyah; Ecep Supriatna (LOSARI DIGITAL, 2026)
Adolescents from Indonesian migrant worker families living in Malaysia face complex psychosocial challenges, including academic pressure, migrant family dynamics, and cross-cultural adaptation processes that may increase the risk of stress and emotional regulation difficulties. Limited access to psychological services in Indonesian schools abroad makes community-based preventive intervention an urgent need. This article aims to describe and analyze the implementation of a culturally sensitive adolescent psychology psychoeducation program as part of a Community Service activity at the Indonesian School of Kota Kinabalu (SIKK), Malaysia. The program involved 20 students, consisting of 12 male and 8 female students, who were assigned by the school to participate based on schedule availability and relevance to the program objectives. The program used a participatory-educational approach with qualitative evaluation through participatory observation, reflective group discussion, participant feedback, and structured field notes. Because the activity did not include quantitative pre-test and post-test scoring, the evaluation focused on qualitative evidence from observed learning processes and participant reflections. The qualitative evaluation showed that participants actively engaged in discussions, recognized adolescent developmental changes, identified psychosocial challenges related to migrant family life, practiced stress-management and emotion-regulation strategies, and demonstrated assertive communication during role-play activities. Participant feedback also indicated that the program was relevant to their daily experiences and helped strengthen self-awareness and confidence in managing psychological challenges. The program offers a contextual school-based psychoeducation model to support the psychosocial well-being of Indonesian migrant adolescents.